THE INFLUENCE OF PERFORMANCE APPRAISAL AND WORK MOTIVATION ON THE PERFORMANCE OF EDUCATIONAL STAFF AT PRIVATE UNIVERSITY X IN BANDUNG CITY - Stefanus Aries T.W.; Nina Nurani (Journal of Social and Economics Research, 2024)
This study was conducted on 165 Permanent Educational Staff at Private University X in Bandung using multiple regression analysis. The results of the study indicate that: 1) The Performance Assessment perceived by the Educational Staff at Private University X in Bandung has good criteria. The Work Motivation perceived also has good criteria, but the Performance perceived has less favorable criteria. 2) Partially, Performance Assessment has a significant effect on the Performance of the Educational Staff. 3) Partially, Work Motivation also has a significant effect on the Performance of the Educational Staff. 4) Simultaneously, Performance Assessment and Work Motivation have a significant effect on the Performance of the Educational Staff at Private University X in Bandung.